The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/imj.13318
|View full text |Cite
|
Sign up to set email alerts
|

Assessing understanding of individual risk and symptoms of progressive multifocal leukoencephalopathy in patients prescribed natalizumab for multiple sclerosis

Abstract: Natalizumab is associated with an increased risk of PML. Early detection and treatment of PML results in improved patient outcomes. Patient knowledge and co-partnership in the utilisation of PML risk tools is relevant in ensuring early detection. Our findings question the ability of currently sanctioned tools to inform patients of basic knowledge of PML and their risk of developing PML. A future study with a repetitive education approach and repeating the questionnaire at multiple time points would be of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Although a higher proportion of PAC recipients identified PML as a potential risk of rituximab than nonrecipients, overall, patients had poor knowledge of PML, showing that the PAC may only contribute to patient knowledge to a limited extent. These results were consistent with those of a previous study evaluating the effectiveness of a PAC in educating patients receiving natalizumab on the risk of PML, which showed that only 16/37 patients (43.2%) who received the PAC answered all PML basic knowledge questions correctly 15. Reaching more patients with the PAC information andimproving knowledge retention are important goals for HCPs, patients, regulators, and MAHs.…”
supporting
confidence: 91%
“…Although a higher proportion of PAC recipients identified PML as a potential risk of rituximab than nonrecipients, overall, patients had poor knowledge of PML, showing that the PAC may only contribute to patient knowledge to a limited extent. These results were consistent with those of a previous study evaluating the effectiveness of a PAC in educating patients receiving natalizumab on the risk of PML, which showed that only 16/37 patients (43.2%) who received the PAC answered all PML basic knowledge questions correctly 15. Reaching more patients with the PAC information andimproving knowledge retention are important goals for HCPs, patients, regulators, and MAHs.…”
supporting
confidence: 91%
“…Four studies [54][55][56][57] reported on information provided via social media. Della Rosa et al 54 investigated the information available on the social network sites.…”
Section: Shared Decision Making In Msmentioning
confidence: 99%
“…We also recently found that the utility of mandated tools in the initiation of other MS therapy is lacking and does not always result in the degree of comprehension of possible fatal complications that is desired in patients by HCPs. 12 Support bodies also increasingly promote this growing trend of online use. MS Australia encourages online education as a means to connect and support patients with MS, allowing the giving and receiving of practical and emotional assistance.…”
Section: Cme/cne Article • 2017 Series • Numbermentioning
confidence: 99%